Embedding Formative Assessment: A Framework of Strategies in Formative Assessment - Syifa Dwi Mutiah (Peneliti.net, 2023)
As assessment holds an important role in teaching and learning activities. The assessment form and understanding need to be comprehensively mastered by the teachers whether in an online or non-online environment. This study attempted to identify and describe comprehensively the framework of formative assessment strategies as an encompassing orientation of formative assessment strategies implementation promoted by (William & Leahy, 2015). This study reviewed books related to formative assessment strategies implementation. The writer finally traces implication for the future guideline of embedding formative assessment, including the example of the strategies of it. The guideline that appeared in this study was from the grand books of Assessment. three books were involved in this study to collaborate. Those are William & Leahy's book (2015), Lee's book (2017), and Fautley & Savage's book (2010). The result showed that William and Leahy's strategies of formative assessment were in line with Icy Lee (2017) book. However, both of them has a different aspect of the environment, William and Leahy focus on the classroom while Icy Lee specified the strategies in the writing area. Additionally, the book of Savage stimuli the further study to elaborate more on the strategies in the online environment